Serum perfluoroalkyl substances (PFAS)and risk of various allergies in adolescents. The Tromsø study Fit Futures in Northern Norway - Averina, Maria; Brox, Jan; Huber, Sandra; Furberg, Anne-Sofie; Sørensen, Martin (Environmental Research, 2019)
Background: Exposure to environmental pollutants may contribute to the development of asthma and other allergies. The aim of this study was to investigate possible associations between asthma and other allergies with exposure to perfluoroalkyl substances (PFASs) in adolescents from the Arctic region of Norway. Methods The Tromsø study Fit Futures 1 (TFF1) and 3-year follow-up Fit Futures 2 study (TFF2) included 675 adolescents that completed a questionnaire about health conditions and underwent a clinical examination with blood tests and fractional nitric oxide (FeNO) measurement. Serum concentrations of 18 PFASs were measured by UHPLC-MS/MS method. Results Total PFASs (ΣPFAS) serum concentration over 4th quartile was positively associated with asthma in the TFF1 (OR 3.35 (95% CI 1.54–7.29), p = 0.002). Total perfluorooctane sulfonate (ΣPFOS), linear PFOS (linPFOS), linear perfluorohexane sulfonate (linPFHxS) concentrations over 4th quartiles were associated with 2 times higher odds of asthma in the TFF1. The positive associations between ΣPFAS, ΣPFOS, linPFOS and asthma remained statistically significant in the TFF2. ΣPFAS and linPFHxS concentrations over 3rd tertiles were associated with positive marker of eosinophilic airways inflammation FeNO> 25 ppb. Concentrations of ΣPFOS and linPFOS over 3rd quartiles were positively associated with self-reported nickel allergy (OR 2.25 (95% CI 1.17–4.35) p = 0.016 and OR 2.53 (95% CI 1.30–4.90) p = 0.006, respectively). Allergic rhinitis, self-reported pollen allergy, food allergy and atopic eczema were not associated with PFASs concentrations. Conclusions This study of Norwegian adolescents showed a positive association between several PFASs and asthma, as well as between PFOS and nickel allergy.